2022
DOI: 10.3389/fgene.2022.1015673
|View full text |Cite
|
Sign up to set email alerts
|

Computational genomics insights into cold acclimation in wheat

Abstract: Development of cold acclimation in crops involves transcriptomic reprograming, metabolic shift, and physiological changes. Cold responses in transcriptome and lipid metabolism has been examined in separate studies for various crops. In this study, integrated computational approaches was employed to investigate the transcriptomics and lipidomics data associated with cold acclimation and vernalization in four wheat genotypes of distinct cold tolerance. Differential expression was investigated between cold treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…Moreover, three MTA identified at a lower significance level matched CBF genes at FR-2R, namely CBFIIId-19, CBFIVa-2.2, and CBFIIIa-6.2. What is more interesting is that ICE1 showed 97% sequence identity to orthologous TaICE41 of hexaploidy wheat, and CBFIIId-19 and CBFIVa-2.2 are putatively orthologous to hexaploid wheat genes reported to be induced by vernalization [199,204] (see above). For ICE1 protein, amino acid variation within the DNA-binding bHLH region and/or start of the zipper region resulted in traits such as WFS and low temperature tolerance.…”
Section: Fr-2 In Rye-evidence Of Ice1 Involvement In the Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, three MTA identified at a lower significance level matched CBF genes at FR-2R, namely CBFIIId-19, CBFIVa-2.2, and CBFIIIa-6.2. What is more interesting is that ICE1 showed 97% sequence identity to orthologous TaICE41 of hexaploidy wheat, and CBFIIId-19 and CBFIVa-2.2 are putatively orthologous to hexaploid wheat genes reported to be induced by vernalization [199,204] (see above). For ICE1 protein, amino acid variation within the DNA-binding bHLH region and/or start of the zipper region resulted in traits such as WFS and low temperature tolerance.…”
Section: Fr-2 In Rye-evidence Of Ice1 Involvement In the Tolerancementioning
confidence: 99%
“…Recent studies expanded the investigation of ICE-CBF-COR interconnection with other environmental stimuli with high-throughput functional analysis [78,195,[203][204][205][206]. Guo et al [78] carried out RNAseq and qPCR analysis in wheat tissues under different stress conditions, observing the expression of 53 genes belonging to the ICE-CBF-COR signaling cascade that revealed tissue-specific expression patterns of the ICE, CBF, and COR genes under different stress conditions.…”
Section: Fr-2 In Wheats-cbf Cluster Ploidymentioning
confidence: 99%
“…The CBF TFs, in turn, upregulate the COR group of proteins, which carry out various protective functions – for example, COR14b protects the photosynthetic apparatus after freezing damage ( Rapacz et al., 2008 ), while COR dehydrins play a cryoprotective role during frost-induced desiccation ( Kosová et al., 2011 ). Therefore, numerous transcriptomic and bioinformatic studies have reported increased expression of the ICE-CBF-COR pathway genes in wheat under cold stress ( Li et al., 2018 ; Guo et al., 2019 ; Aleliūnas et al., 2020 ; Pan et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%